Centro de investigación Parque Nacional del Agua Juan Castro Blanco - Avendaño-Ramírez, Karen (Instituto Tecnológico de Costa Rica., 2017)
The current global priority is to preserve our planet. From the perspective of sustainability, it implies a reduction in global warming, eco-footprint, and the protection of natural resources. Water is as important as energy. Water shortage in the world is an issue that requires more urgent addressing than energy distribution, given that it affects people’s quality of life. On July 28th, 2010, in resolution 64/292, the United Nations General Assembly established water and sanity as human rights, stating that pure, drinking wáter and sanity are essential to all the other human rights (UNO, 2010). Due to this, great efforts are made to raise social awareness since saving wáter has become one of the challenges people face nowadays. However, the first step to accomplish this is to protect water resources. Costa Rica has one of the biggest natural protected areas, approximately 13 000 Km2 (26,2%) of its national territory. Juan Castro Blanco National Park was created out of the need to preserve one of biggest (the second biggest) areas with water resources in the northern part of the country. More than 150 communities benefit from the drinking water it provides. Another major activity in this national park is producing hydroelectric energy. 12% of the national production of energy comes from this area. One of the main objectives is preserving, protecting and using resources through a model of sustainability and economical development. PNAJCB has developed research on natural resources, such as forests and endemic species. This dissertation’s main focus is research from the perspective of architecture so that it contributes to the development of infrastructure that facilitates for PNAJCB’s research and tourism. The research process is essential to understand ecosystems, preserve natural resources, and create knowledge to improve the quality of life of our future generations. Here you will find a proposal with sustainable infrastructure that can contribute to developing research in national parks, particularly in PNAJB. it is also encouraged to raise awareness about the importance of sustainable proposals to improve Costa Rican protected areas.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017.
Keywords: Centros de investigación Diseño arquitectónico; Parque Nacional del Agua Juan Castro Blanco; Parques nacionales; Arquitectura